DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING LECTORA INSPIRE FOR INFORMATION AND COMMUNICATION TECHNOLOGY SUBJECT: AN ADDIE-BASED APPROACH - Roikhatus Silma Nadzifa; Fahrur Rozi (STKIP PGRI TULUNGAGUNG, 2026)
The limited use of technology-based instructional media in junior high school settings has negatively affected student engagement and learning outcomes in Information and Communication Technology (ICT) subjects. This study aims to develop interactive learning media using Lectora Inspire for eighth-grade ICT students at SMP Negeri 4 Tulungagung, Indonesia, and to evaluate its feasibility based on expert validation and student responses. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), a systematic instructional design framework widely adopted in educational technology research. The media was validated by two material experts and two media experts, and subsequently tested with 10 students (small group) and 30 students (large group). Feasibility was measured using a percentage-based scoring rubric. Results indicated that material experts rated the media at 76.4% (Feasible), media experts rated it at 75.9% (Feasible), while student responses reached 87.92% (small group) and 92.92% (large group), both classified as Very Feasible. These findings demonstrate that the Lectora Inspire-based interactive media is a viable, engaging, and pedagogically appropriate tool for ICT learning at the junior secondary level. The study contributes to the growing body of research on authoring-tool-based e-learning development in developing-country educational contexts, and highlights the potential of offline-compatible interactive media to address infrastructure challenges in Indonesian schools